Fexofenadine Protects Against Intervertebral Disc Degeneration Through TNF Signaling - Liu, Kaiwen; Wei, Jianlu; Li, Guohua; Liu, Ronghan; Zhao, Dawang; Zhang, Yuanqiang; Shi, Jie; Xie, Qing; Cheng, Lei (Frontiers in Cell and Developmental Biology, 2021)
Objective：Fexofenadine（FFD） is an antihistamine drug with anti-inflammatory effect. Intervertebral disc degeneration process is involved in inflammation in which tumor necrosis factor-α(TNF-α) plays an important role. This study aims to investigate the role of FFD in the pathological process of intervertebral disc degeneration. Methods：Safranin O staining was used for the measurement of cartilageous tissue in disc. Hematoxylin-Eosin (H&E) staining was taken to determine the disc construction. Rat needle puncture model was taken advantage for examining the role of FFD in disc degeneration in vivo. Western Blotting assay as well as immunochemistry and immunoflurence staining was used for determination of inflammatory molecules. ELISA assay was performed to detect the release of inflammatory cytokines. Real-time PCR assay was analyzed to determine the transcriptional expressions of molecules. Results：Elevated TNF-α resulted in inflammatory disc degeneration, while FFD protected against TNF-α-induced intervertebral disc degeneration. Mechanism study found FFD exhibited its disc protective effect through at least two pathways. a) FFD inhibited TNF-α-mediated extracellular matrix (ECM) degradation; b) FFD rescued TNF-α induced inflammation in disc degeneration. Furthermore, present study found FFD suppressed TNF-α mediated disc degeneration via cPLA2/NF-κB signaling pathway. Conclusions: FFD provided another alternative for treating disc degeneration through a novel mechanism. Additionally, FFD may also be a potential target for the treatment of other inflammatory related diseases, including intervertebral disc degeneration.